2020
DOI: 10.4103/jfmpc.jfmpc_63_20
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diabetes among patients and the assessment of the awareness of the bidirectional relation between diabetes and periodontal disease

Abstract: Aim: To assess the extent of self-awareness and knowledge of diabetes and its association with periodontal disease among patients seeking dental care. Materials and Methods: Data were collected in the form of a questionnaire from 150 consecutive adult patients from the outpatient department of Saveetha Dental College in Chennai, India. Complying patients were tested for diabetes mellitus by checking their random blood sugar and the results were correlated with the quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Over the years, essential evidence has shown that diabetes is a risk factor for impaired periodontal health. Studies that have focused on examining the relationship between diabetes and periodontal disease have shown an increase in incidence; this association that has increased scientific interest [ 36 , 37 ]. Patients with diabetes generally have a higher prevalence of periodontal disease than the healthy population, with a clear relationship between diabetes and different clinical conditions related to periodontal parameters.…”
Section: Periodontitis and Diabetes Mellitusmentioning
confidence: 99%
“…Over the years, essential evidence has shown that diabetes is a risk factor for impaired periodontal health. Studies that have focused on examining the relationship between diabetes and periodontal disease have shown an increase in incidence; this association that has increased scientific interest [ 36 , 37 ]. Patients with diabetes generally have a higher prevalence of periodontal disease than the healthy population, with a clear relationship between diabetes and different clinical conditions related to periodontal parameters.…”
Section: Periodontitis and Diabetes Mellitusmentioning
confidence: 99%